PROFESSIONALLY IMPORTANT QUALITIES OF A FUTURE SPECIALIST IN INTERNATIONAL LAW - Ladohubets, Nataliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article analyzes the essence and theoretical foundations of the concept of "professionally important qualities of a future specialist in international law" taking into account modern professional requirements for future specialists. The purpose of the article is to analyze the scientific definition of the concept of "professionally important qualities of a future specialist in international law." A number of domestic and foreign scientific, scientific and journalistic sources were analyzed, in which special attention was paid to the concept of "professionally important qualities". Using scientific knowledge methods: theoretical (study, analysis, synthesis, comparison, generalization of scientific literature on the research problem, systematization and generalization of the obtained data), which made it possible to clarify a number of questions of both a theoretical and methodological nature regarding the professionally important qualities of future specialists in international law, taking into account the peculiarities of the modern stage of the development of society. The researching results, conducted on the basis of the theoretical understanding of scientific works, defined the concept of "professionally important qualities of a future specialist in international law" showed that the conducted theoretical and methodological discourse of the concept of "professionally important qualities of future specialists in international law" is a complex of personal properties, individual psychophysiological and socially important qualities that contribute to the successful performance of future professional activities, solving complex specialized tasks with multi-vector uncertainty, personal and professional growth and improvement